SISTEM PENDETEKSI KESUBURAN TANAH MENGGUNAKAN NODEMCU ESP32 BERBASIS INTERNET OF THINGS: DETECTIESYSTEEM VOOR BODEMVRUCHTBAARHEID MET BEHULP VAN NODEMCU ESP32 OP BASIS VAN INTERNET DER DINGEN - Farhani Farhani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
This research aims to design and build an Internet of Things (IoT)-based soil fertility detection system using the NodeMCU ESP32 microcontroller. The system is equipped with three main sensors, namely soil pH sensor, capacitive soil moisture sensor, and TCS3200 color sensor. The data obtained is sent in real-time and displayed through a web interface and Arduino IDE serial monitor. The system is able to classify soil fertility based on pH, moisture, and soil color values, and provide recommendations for food crops such as rice, corn, green beans, and cassava. This research uses a quantitative method by taking soil samples from four different locations in North Aceh District: coastal, agricultural rice fields, mountains, and highlands. The test results show the system is able to provide accurate fertility classification and crop recommendations according to soil conditions in each location. The average system response time from sensor reading to data display is 1 second, indicating responsive and real-time system performance. Although the free web version does not yet support soil color display (RGB), all complete data can be accessed through the serial monitor. This system has the potential to be an innovative solution in supporting farmers in digital data-based decision-making to improve agricultural productivity.